DEVELOPMENT OF SAW (SIMPLE ADDITIVE WEIGHTING) METHOD FOR DECISION SUPPORT SYSTEM OF SEMBAKO PRICE CONTROL - Wulandari, Sri; Permana Wibowo, Adityo (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2019)
The Supporting System The decision to control basic food prices at the fisheries and forestry service is a system designed to assist relevant agencies in seeing prices of basic necessities which tend to increase at any time. At first the relevant agencies do recap calculations by storing data and still counting manually, so it requires a longer time, with the existence of this system it is expected to be able to help and provide solutions for consideration of decision making in accordance with the right calculations.The decision support method of calculation used is the SAW method that takes the greatest value to be used as a decision-making ranking. In addition, other methods used are data collection methods by observation and interviews to identify problems in developing support systems for basic food price control decisions. Model design is described using data flow diagrams (DAD) and entity relationship diagram (ERD).The system developed is able to record, calculate and provide alternative solutions effectively for relevant agencies. With this system, agencies are expected to be able to process the calculation of basic food prices better, select more accurate decisions, and take more effective alternative solutions.